The third industrial revolution :how lateral power is transforming energy, the economy, and the world - Rifkin, Jeremy. (Palgrave Macmillan, 2011)
"We are undergoing a historical transformation in the way we create and disseminate energy. Together, Internet technology and the reality of renewable energy are creating a new type of electrical grid, one in which energy is stored and distributed on an individual basis. Soon, hundreds of millions of human beings will be generating their own green energy in their homes, offices and factories, and sharing it, just as they now create their own information and share it on the Internet. In just a few years, millions of buildings and even cities will become energy self-sufficient, signaling the end of our reliance on fossil fuels. This transformation is already underway in Europe, where author Jeremy Rifkin serves as EU advisor on a project that will revolutionize the continent's energy supply, with Asia to follow. We even see shades of it in Texas, Colorado, and California, where electrical companies will be laying down parts of the Smart Grid over the next several years. But it's not just about the promise of clean energy. Rather, this "Energy Internet" will fundamentally change every aspect of the way we work and live. It will foster continental markets and the creation of continental political unions to oversee new expansive commercial opportunities. It will signify the end of needless wars fought over energy sources, and the dawning of an era of true international cooperation. Finally, it offers the hope that we can get to a post-carbon era by mid century and avert catastrophic climate change. Here, Rifkin explains how the United States can embrace this ambitious vision of the future, end its decades-old crisis over foreign oil, and ensure its continued status as world power. He also paints an accessible, anecdotal picture of what our lives will look like in this new global order-if we can summon the political will to join it"--